Safety of Oral Food Challenges in Early Life - Katherine Anagnostou (MDPI AG, 2018)
Oral food challenges are becoming more frequent in the allergy clinic due to an increased demand related to early food introduction in infants. We examined the safety of oral food challenges in 18 high-risk infants with prior allergic reactions, as well as infants with no known exposure to the food, presenting consecutively in a dedicated food allergy clinic for an oral food challenge. Foods challenged included peanut, tree nuts, sesame, baked egg, baked milk, and soy. A total of 17/18 (94%) infants had a negative challenge. Only 1/18 (6%) had a positive challenge, and in this case, symptoms were mild and limited to the skin. Our results suggest that food challenges in infants and young children up to the age of 2 years are safe with symptoms limited to the skin when reactions occur. In our cohort, the large majority of food challenges were negative, with most infants being sensitized rather than allergic to the food. Larger studies are needed to confirm this finding.